Diabetes Vs Silent Killer: Magnitude and Allied Factors of Hypertension Among Diabetic Patient at Hidar 11 Hospital, Akesta, Ethiopia - Prem Kumar (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Hypertension is a masked silent killer and one of the perilous non-communicable diseases. Hypertension and diabetes generally coexist because they share similar risk factors, including being overweight, following an unhealthy diet, and living an inactive lifestyle. Despite being preventable disease, diabetes and hypertension fall among top 10 leading causes of death globally. Diabetes mellitus has rapidly become a major threat in almost all developed and developing countries. Objective: To determine the prevalence and allied factor of hypertension among diabetic patients attending follow-up at Hidar 11 hospital Akesta, June 2017G.C. Methodology Institutional based cross sectional design was used to assess the prevalence and associated factor of hypertension among DM patients. A total of 388 patients were included using simple random as non probability sampling. The blood pressure measurement was collected using manual BP apparatus, patient’s height and weight was measured to calculate the BMI. Structured questionnaire was used to gather associated socio-demographic data. Results From a total of 388 diabetic patients 175(45.1%) of them have hypertension. significantly association with type of DM medication, stress, hyperglycemic control, and alcohol consumption. Conclusion: The prevalence of hypertension among DM patients was in higher end. The prevalence of hypertension among diabetic patients was 45.1% is much higher, and duration of DM and anti-diabetic medication consumers had an association in causing hypertension.